IMPROVING THE CAPABILITY OF STRUCTURE MASTERY THROUGH CONTEXTUAL LEARNING IN THE FIRST SEMESTER STUDENTS OF ENGLISH EDUCATION AT UNIVERSITAS MUHAMMADIYAH SURAKARTA - Sumayah Sumayah; Tri Wulandari (Prosiding University Research Colloquium, 2022)
Contextual teaching is a contextual teaching learning, namely learning that helps lecturers in relating the material being taught to students' real-world situations and encourages students to make connection between their knowledge and its application to their daily lives. This involves seven main components of effective learning, namely; constructivism, questioning, inquiry, learning community, modeling, reflection and authentic assessment n English Education students at Universitas Muhammadiyah Surakarta. This research was carried out at Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta in approximately four months from August 2021 to November 2021. The subjects of this study were students of the first semester of Sentence Building. Research data sources are from lecturers and students. The data are texts of the assignments and tests and the results of analysis answers. Data were collected through the collection of tasks and tests, and observations, then validated using triangulation of methods and data sources. The data analysis technique uses a calculation formula. The data of the impact of the implementation are analyzed by describing and presenting. The use of contextual analysis improves students' understanding. The results obtained were as many as 20 students scored above 70 or 76.92% and 6 students achieved standard indicator scores or about 23%. This achievement had met the criteria for indicators of success (70%). as much as 1.15% and the number of students who managed to increase by 7%Keywords: Sharia Compliance, BPRS, pandemic covid-19, murabaha